Increased expression of platelet-derived growth factor associated protein-1 is associated with PDGF-B mediated glioma progression. (September 2016) - Sharma, Vinay Kumar; Singh, Anand; Srivastava, Sandeep Kumar; Kumar, Vignesh; Gardi, Nilesh Laxman; Nalwa, Aasma; Dinda, Amit Kumar; Chattopadhyay, Parthaprasad; Yadav, Savita
Graphical abstract: Expression of PDAP-1 increases with the degree of malignancy in human gliomas and regulate the expression of PDGF and its downstream genes. siRNA mediated knockdown of PDAP-1 in combination of anti PDGF antibody induce apoptosis through Caspase activation. Co-expression of PDAP-1 with PDGF-B is critical for the glioma cell proliferation and PDAP-1 could be considered as a potential therapeutic target. Highlights: ⿢ The expression of PDAP-1 is associated with malignancy of human gliomas. ⿢ Knockdown of PDAP-1 reduces the expression of PDGF-B and its downstream genes/proteins. ⿢ PDAP-1 knockdown in combination of anti PDGF antibody is able to induce apoptosis and reduces the rate of glioma cell proliferation. ⿢ PDAP-1 interacts with PDGF-B in the cytoplasm of glioma cells and modify the biological activity of PDGF-B. Abstract: The current treatment therapies available for malignant gliomas are inadequate. There is an urgent need to develop more effective therapies by characterizing the molecular pathogenesis of the disease. Over expression of platelet-derived growth factor (PDGF) ligands and receptors have been reported in malignant gliomas. Platelet-derived growth factor associated protein-1 (PDAP-1) is reported to modulate the mitogenic activity of PDGF ligands, but to date, there is no information concerning its role in PDGF-mediated glioma cell proliferation. This study aimed to characterize the role of PDAP-1 in PDGF-mediated glioma proliferation. The expression of PDAP-1 was observed to be significantly increased (p< 0.05) in grade IV glioma tissue and cell lines compared to grade III. siRNA-mediated knockdown of PDAP-1 reduced the expression of PDGF-B and its downstream genes (Akt1/Protein kinase B (PKB) and phosphoinositide-dependent kinase-1 (PDK1) by up to 50%. In PDAP-1 knockdown glioma cells, more than a twofold reduction was also observed in the level of phosphorylated Akt. Interestingly, knockdown of PDAP-1 in combination with PDGF-B antibody inhibited glioma cell proliferation through activation of Caspase 3/7 and 9. We also demonstrate that PDAP-1 co-localizes with PDGF-B in the cytoplasm of glioma cells, and an interaction between both of the proteins was established. Collectively, these findings suggest that the expression of PDAP-1 is associated with disease malignancy, and its inhibition reduced the proliferation of malignant glioma cells through down-regulation of PDGF-B/Akt/PDK1 signaling. Thus, this study establishes PDAP-1 as an effecter of PDGF signaling in glioma cells and suggests that it could also be a promising therapeutic target.